(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Breast cancer is one of the leading causes of death for women worldwide. It is a multilevel disease characterised by aberrant breast tissue development. As a patient's stage progresses, his or her odds of being treated and of surviving decreases. As a result, it is critical to identify and treat breast cancer early. Microwave imaging for breast cancer detection is an intriguing technology for detecting tumours, and it has a lot of benefits over other breast cancer detection methods that are already in use.UWB technology is mainly widely prescribed for usage in such an applications because to its special qualities such as short-range, non-ionizing, and broad bandwidth have used a UWB antenna sensor network to image and detect breast cancer. Non-ionizing radio waves are one of them. Its benefits are adaptability, a low-cost technology, and human body safety. For receiving and sending microwaves, microwave vision relies on a microstrip patch antenna. As the term suggests, a micro strip patch antenna is a small, light antenna. Microstrip patch antennas are classified as flexibility or non-flexible dependent on the substrate surface.They designed a simple recursive antenna (peano patch antenna) for the Ultra-Wideband frequency (6.744 GHz) (-42.657 dB).The antenna options for breast imaging on a transmitter is an antenna array composed of 18 antennas. The antenna is designed in a circular shape to allow it to face exactly at the image of the breast for greater disease diagnosis.